SOUTH CAROLINA VOTER ATTITUDES TOWARDS PROPERTY TAX: RESULTS FROM A SURVEY ON TAX SALIENCE AND ESCROW - Hayashi, Andrew T. (Economics and Statistics Research Journal (ESRJ), 2023)
Despite its importance as a funding source for local governments, the property tax remains unpopular among citizens. This paper explores how different payment formats for property taxes may impact citizens’ willingness to support property taxes to fund public schools. Specifically, it considers whether payment by escrow, where a portion of the homeowner’s projected annual property tax bill is rolled into their monthly mortgage payment, may lead to higher support for school tax increases than payment of property taxes in one annual lump-sum amount. Using survey data from a randomly selected sample of South Carolina voters, the study finds that escrowing taxpayers do support increases in school property tax more than non-escrow taxpayers. However, the study also finds that escrowing homeowners do not display significantly lower knowledge of the actual costs of school taxes compared to non-escrow payers, indicating that school property tax costs are poorly understood by most voters, regardless of the payment format. The paper concludes that tax presentation via escrow impacts tax attitudes through lowering the salience of tax costs to homeowners who pay via this method, while non-escrow payers are more primed to react to the possibility of a tax increase via the higher salience of the issue to them. The paper suggests that tax presentation exerts an independent effect on support for increasing property taxes to pay for public schools, even when controlling for various demographic and control variables.